Particle swarm optimised fuzzy controller for chargingdischarging and scheduling of battery energy storage system in MG applications - Faisal M.; Hannan M.A.; Ker P.J.; Rahman M.S.A.; Begum R.A.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Battery management systems; Battery storage; Charging (batteries); Controllers; Cost reduction; Electric power transmission networks; Electric power utilization; Fuzzy control; Fuzzy logic; Membership functions; Microgrids; Particle swarm optimization (PSO); Scheduling; Secondary batteries; Temperature control; Battery energy storage systems; Battery temperature; Conventional systems; Distributed sources; Fuzzy logic controllers; Mathematical calculations; Particle swarm optimisation; Scheduling controllers; Electric power system control